Utilização de sistema colunas d’água oscilantes no controle de pitch de um casco FPSO - Costa, Daniel de Oliveira (2019)
This work presents a continuation of the study about reduction of pitch response of FPSO platforms carried out at the Laboratory of Waves and Current (LOC/COPPE), using a system of oscillating water columns combined to the concept of dynamic vibration absorbers. A mathematical model is proposed to describe the behavior of the flow within the moonpools from the concept of Oscillating Water Columns, incorporating it into numerical procedures to evaluate the response of the vessels with moonpools, considering their influence over the potential coefficients as well as the viscous effects of the flow inside of them. An extensive theoretical, numerical and experimental study was carried out for the purpose of improving the proposed system, with the achievement of an ideal configuration to minimize the pitch response of FPSO platforms as final objective. The experiments were performed at the Laboratory of Waves and Current (LOC/COPPE) at the Federal University of Rio de Janeiro (UFRJ) and the numerical analysis through a Potential Theory based software.